Experiences of lifestyles in the elderly and their relationship to health - Santacruz, Rita Aguilar; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana - Facultad de Enfermería, 2011)
The study was carried out through an interview to two focal groups, each one made up of ten (10) elderly people, who regularly attendend a thirdage program in the Kennedy neighborhood located in the south-western area of Santa Fe de Bogotá. The focal interview was done in five sessions during which participants reconstructed lifestyle and health experiences related to their daily life activities in terms of occupation, physical activity, recreation, food habits and intra family relationships.